Farmer selection of drought‐tolerant enset landraces reduces trait diversity in drier environments - Chase, Rachel; Borrell, James S.; Rodenburg, Jonne; Roux, Nicolas; Wendawek, Abebe; Büchi, Lucie (Wiley, 2025)
Increasing drought stress driven by climate change presents a significant challenge to global food security, requiring crop adaptations. Indigenous knowledge and sustainable practices in drought‐prone agricultural systems may offer effective climate adaptation strategies. This study investigates the functional traits associated with the reported drought tolerance of enset ( Ensete ventricosum ), a multipurpose Ethiopian staple crop providing food security to more than 20 million people. Through field surveys and farmer interviews along three aridity gradients in southwest Ethiopia, we determined how domestication and farmer cultivation choices have shaped enset trait and landrace diversity. We measured 12 morphological and physiological traits of 430 cultivated enset plants on farms and a subset of traits of 30 wild enset plants. We also conducted interviews on farmers' knowledge of drought and enset, and how it influenced their choice of landraces. We showed that domestication reduced trait variance in cultivated enset and lowered landrace diversity in drier environments. Farmers in drier areas chose landraces with drought tolerance traits, resulting in trait differentiation between wetter and drier farms. Cultivated enset exhibited lower stomatal density and a narrower aridity niche compared to wild enset, suggesting adaptation to reduce water loss. We also found increased leaf wax coverage, leaf number, leaf temperature differential and plant height growth rate and reduced stomatal conductance on drier farms. Our findings are globally relevant, highlighting that climate adaptation and farmer selection may reduce trait and genetic diversity in drier environments, potentially resulting in less adaptative capacity under climate change.